War and the law of nations : a general history - Neff, Stephen C. (Cambridge ; New York : Cambridge University Press, 2005)
Tracing war as a legal concept from Roman times through to the twentieth century, Stephen Neff reveals its various roles as a law-enforcement operation, duel between states and a "crime against the peace." He also considers the post World War II definition of war as an international law-enforcement mechanism under U.N. auspices. Although unsuccessful, this attempt did help transform war into a humanitarian, rather than a policy problem. This book interests historians, students of international relations and international lawyers.
Part I. War as Law Enforcement (to 1600) -- 1. Ares and Athena -- 2. Loving enemies and hating sin -- Part II. New Forces Stirring (1600-1815) -- 3. War in due form -- 4. Dissension in the ranks -- Part III. War as State Policy (1815-1919) -- 5. Collisions of naked interest -- 6. Tame and half-hearted war: intervention, reprisal and necessity -- 7. Civil strife -- Part IV. Just Wars Reborn (1919- ) -- 8. Regulating war -- 9. Farewell to war? -- 10. New fields of battle.
Includes bibliographical references (pages 399-421) and index.
Keywords: War (International law) -- History; Guerre -- Histoire; Guerre (Droit international) -- Histoire; War (International law); History